From the Efficiency of Berlese Tullgren Funnel to the Spatiotemporal Variation of Two Uropodina Genera, Afrotrachytes Kontschán, 2006 and Trachyuropoda Berlese, 1888 (Acari, Mesostigmata) in Côte d’Ivoire - N’Dri, Julien Kouadio; Guéi, Arnauth M.; Hance, Thierry; Yaco, Joseph G.; Ahui, Jean-Luc D.S.; Andrac, Henri M. (JOURNAL OF ADVANCES IN BIOLOGY, 2018)
Due to their interaction with many other small Arthropods, Uropodina mites can be considered as good indicators of soil fauna of forest litter. In order, to better understand their distribution and phenology according to forest type four sites from primary forest to plantations were sampled in 2008 in Côte d’Ivoire: 1- the Lamto savannah (6°13’ N, 5°02’ W), 2- Oumé primary forest (6°31’ N, 5°30’ W), 3- Oumé teak plantation (6°31’ N, 5°30’ W) all situated in the Sudanese domain and finally, 4- the Taï primary forest (5°45’ N, 7°07 W) located in the Guinean domain. After a preliminary study devoted to the efficiency of Berlese Tullgren funnel, the spatiotemporal variation of two Uropodina genera - Afrotrachytes Kontschán, 2006 and Trachyuropoda Berlese, 1888 - was assessed. We hypothesized that the abundance of Uropodina would be higher in primary forest and lower in savannah and monospecific plantation. Whatever the season, we expected that the abundance of Uropodina would decrease with soil depth and would vary along transect. On each site, 15 sampling points were allocated over a 14-m transect with 1m intervals between two consecutive points. For each sampling point, 9 cores (litter, 0-5, 5-10, 10-15, 15-20, 20-25, 25-30, 30-35 and 35-40 cm) were taken with a steel corer (Ø 3.5 cm). Thus, a total of 1,080 soil cores were collected over two sampling periods from January to March 2008 (dry season) and August to October 2008 (rainy season). Soil physico-chemical parameters were also characterized. Mites were extracted using the Berlese-Tullgren funnels for one week after testing the extraction duration in a preliminary study. The bulbs lighting as soon as the soil cores were placed in Berlese Tullgren gave better results regarding the abundance of extracted mites. The results showed that the abundance of Afrotrachytes sp and Trachyuropoda sp was higher in rainy season, and varied significantly through the sites, whatever the season. The highest abundances of Afrotrachytes sp were observed in Oumé primary forest whereas those of Trachyuropoda sp were recorded in Oumé primary forest, and in Lamto savannah, whatever the season. Apart from the distribution of Trachyuropoda sp in dry season, the abundance of Afrotrachytes sp and Trachyuropoda sp was greater in the topsoil (litter and 0-5 cm) and decreased with soil depth. The abundances of Afrotrachytes sp and Trachyuropoda sp did not follow a normal distribution along the transects. The season-soil depth interaction affected significantly the abundance of Trachyuropoda sp whereas the bulk density (dry season and rainy season), soil depth (dry season), carbon / nitrogen ratio (dry season) impacted significantly the abundance of Afrotrachytes sp. This first study highlighted the spatiotemporal variation of Uropodina in Côte d’Ivoire. However, taking into account of the different dispersal agents in future studies would help us to better understand their abundance and distribution along different habitats, as well as their role as biological control agents.